Pelatihan Guru dalam Menyusun Modul Ajar Ppada Kurikulum Merdeka Melalui Aplikasi Canva di SD NU Padomasan - Nafi’ah, Jamilatun; Aini Sulthon, Elok (Universitas Al-Falah As-Sunniyah Kencong Jember, 2023)
The launch of the Independent Curriculum in Indonesia also provides flexibility and necessity for teachers in developing a learning that is more creative, innovative and applicable in compiling teaching modules. In this case, creativity and mastery of technology are also needed so that teachers remain adaptive to digital developments. Through the Canva application, teachers can develop innovation and creativity in compiling teaching modules to make it easy, interesting and more directed. However, in its implementation, there are still limitations of teachers in maximizing the use of technology including the Canva application in their learning. So that training is needed according to the needs in compiling teaching modules through the use of the Canva application. The target of service in this training activity is teachers at SD NU, Padomasan District, Jember Regency. The methods used in the implementation of community service activities are the Lecture, Demonstration and Practicum Methods. The target and result of this service is that teachers can maximize technology through the Canva application in maximizing their learning process..